PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN DANA ALOKASI KHUSUS TERHADAP BELANJA MODAL (PADA PEMERINTAH PROVINSI BANTEN PERIODE 2011-2015) - ARRY EKSANDY; MOHAMAD ZULMAN HAKIM; EKAWATI EKAWATI (Universitas Muhammadiyah Tangerang, 2018)
The purpose of this research is to know the effect of Local Revenue, General Allocation Fund, Special Allocation Fund to Capital Expenditure. The research period used is 5 years in the period 20112015. The study population covers all the existing Kota / Kabupaten in Banten Province for the period of 2011-2015. Sampling technique using saturated sampling technique. Based on the predetermined criteria, the number of samples 8 Kota and 8 Kabupaten. The type of data used is secondary data obtained from the official website of Banten Province. Data analysis method used is panel data regression analysis. The results of this study indicate that the General Allocation Fund affects the Capital Expenditure, while the Original Revenue and Special Allocation Fund has no effect on Capital Expenditure. Keywords: Local Revenue, General Allocation Funds, Special Allocation Funds, Capital Expenditures